Snow White - Webb, Marc; Zegler, Rachel, 2001-; Gadot, Gal ([Place of publication not identified] : Sony Pictures Home Entertainmt, 2025)
Experience this musical, live-action reimagining of Walt Disney?s groundbreaking animated classic. Follow Snow White?s adventure as she journeys into magical woods to escape the Evil Queen and meets the beloved Bashful, Sleepy, Sneezy, Happy, Dopey, Grumpy and Doc who join her quest to restore the kingdom.
new dvd 2025 summer.
Keywords: Fantasy; Drama; Action; Adventure